Identifying transfection efficiency and cartilaginous markers expression in chondrocytes overexpressed with SRY (Sex Determining Region Y)-Box 9 (SOX9) gene: A preliminary analysis in an in vitro model - Md Nazir, Noorhidayah; Mohammad, Mohd Yusof; Ahmad Radzi, Muhammad Aa’zamuddin; Hashim, Rosyafirah; Mat Nawi, Nur Farhana; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Zainol, Ismail; Zamli, Zaitunnatakhin; Shaban, Munirah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Gene transfer technology offers innovative biological repair strategies for cartilage regeneration in tissue engineering. Non-viral vector-mediated gene transfers present certain advantages over viral vector methods particularly in terms of safer delivery of the intended therapeutic DNA into cells. It has been well documented that chondrocytes lose its chondrogenic phenotypes when serially expanded in monolayer cell culture. Previous studies suggested that overexpression of SOX9, a cartilage-specific transcriptional factor through non-viral methods promotes chondrogenic differentiation of certain cells. Hence, this preliminary study aimed to assess transfection efficiency and cartilaginous markers expression in monolayer cultured chondrocytes overexpressed with SOX9 gene. With the approval by the Institutional Animal Care and Use Committee (IACUC) IIUM, articular cartilage samples were harvested from the lateral and medial femoral condyles of two rabbits. The samples were washed and underwent enzymatic digestion to isolate the chondrocytes. The chondrocytes were cultured, serially expanded and transfected with SOX9-expressing plasmid at passage 1 using three transfection reagents i.e. Lipofectamine® 2000, Lipofectamine® 3000 and jetPRIME®, according to the manufacturers’ protocols. Plasmid containing green fluorescent protein (GFP) was co-transferred to the cells. Transfection efficiency was determined by estimating the percentage of GFP-positive cells under fluorescence microscopy, CytellTM Cell Imaging System 24-hour post-transfection based on the manufacturers’ recommendation. Collagen type II, SOX9 and collagen type I genes expressions were assessed at passage 1, 2 and 3. The results indicate that Lipofectamine® 3000 showed better transfection efficiency than Lipofectamine® 2000 and jetPRIME®. Cartilaginous markers i.e. collagen type II and SOX9 were constantly expressed in all samples throughout all passages. Collagen type I was also co-expressed in the cultured chondrocytes. Taken together, short-term SOX9 overexpression have the potential to sustain chondrogenic phenotypes of the serially expanded chondrocytes. The findings perhaps, can be an indication that SOX9 facilitates chondrogenesis and thus may have potential implications in cartilage tissue engineering.